Leben lesen Zur Theorie der Biographie um 1800 - Heinrich, Tobias (Böhlau, 2016)
This volume represents the first extensive study on German theoretical approaches to biographical writing at the end of the Eighteenth Century. Following key figures in German Enlightenment like Johann Gottfried Herder, Friedrich Schlichtegroll and Daniel Jenisch, this book traces the attempt to establish biography as a central genre in comprehensive hermeneutic world view.